New Current-Mode Bandpass Filters Using Three Single-Output ICCIIs - Ahmed M. Soliman (Active and Passive Electronic Components)
New current-mode bandpass filters using three single outputs inverting second generation current conveyors (ICCII) are introduced. The first circuit uses two ICCII+ and one ICCII−, and realizes an inverting bandpass response. This circuit has one floating resistor and no independent gain control. The second circuit uses three ICCII− and realizes a noninverting bandpass response. The third circuit uses three ICCII+ and realizes also a noninverting bandpass response. The second and third circuits employ four grounded resistors and two grounded capacitors and have independent control on Q and on the center frequency gain by varying a single grounded resistor. Spice simulation results using 0.5 um CMOS transistors are included to support the theoretical analysis.